PENINGKATAN HASIL BELAJAR TEMATIK TERPADU TEMA 2 DENGAN MODEL PROBLEM BASED LEARNING DI SD KARTIKA 1-11 PADANG - Ilham, Roky; Sukma, Elfia; Fachrudin, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis research aims to improve student learning outcomes in an integrated thematic learning by applying problem-based learning in class IV SD Kartika I-11 Padang. This research is a classroom action research (PTK) which uses qualitative and quantitative approaches. Conducted in two cycles, with three meetings includes four stages: planning, implementation, observation, and reflection. The subjects were students of class IV SD Kartika 1-11 Padang numbered 20 people. The results showed that the learning plan 2 theme by using a model of Problem Based Learning can improve the process and student learning outcomes.Keywords: learning outcomes, Problem Based Learning models